If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5c + -3 = 6c Reorder the terms: -3 + 5c = 6c Solving -3 + 5c = 6c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-6c' to each side of the equation. -3 + 5c + -6c = 6c + -6c Combine like terms: 5c + -6c = -1c -3 + -1c = 6c + -6c Combine like terms: 6c + -6c = 0 -3 + -1c = 0 Add '3' to each side of the equation. -3 + 3 + -1c = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1c = 0 + 3 -1c = 0 + 3 Combine like terms: 0 + 3 = 3 -1c = 3 Divide each side by '-1'. c = -3 Simplifying c = -3
| -64=6b-4 | | 2n-7=5n-10 | | 13-3(5x-4)=-2 | | 6x+48=8x+8 | | -4x-5x=27 | | -64=6b | | 1568/7.28=h | | -8u+3(u-4)=-22 | | 3x^2-12x+31=22 | | 4a-2=6a | | 3y-5=46 | | (5+x)(3+x)(x)= | | 4(x+8)-6=26 | | -2x-12=-6(x+4) | | -3x^2+30X+90=0 | | 3x=10+7x | | 3x-4=7+4 | | -9=36+6 | | 2y+y-3=6 | | -6t+18=30 | | -11x-1=87 | | 3x=7x-10 | | 1.24+5p= | | 4(v+3)-6u=18 | | p(x)=x^3-xfindp(5) | | 5a-6=3a+20 | | 3x+5(x-8)=4(x-5)-12 | | 49.5=9.h/2 | | y^2-y-5=y-2 | | 4v+12-6u=18 | | (6x)-(5x-48)= | | 5x-7=-62 |